G-quadruplex-based aptamers against protein targets in therapy and diagnostics - Platella, Chiara; Riccardi, Claudia; Montesarchio, Daniela; Roviello, Giovanni N.; Musumeci, Domenica (Biochimica et biophysica acta. General subjects, 2017)
Nucleic acid aptamers are single-stranded DNA or RNA molecules identified to recognize with high affinity specific targets including proteins, small molecules, ions, whole cells and even entire organisms, such as viruses or bacteria. They can be identified from combinatorial libraries of DNA or RNA oligonucleotides by SELEX technology, an in vitro iterative selection procedure consisting of binding (capture), partitioning and amplification steps. Remarkably, many of the aptamers selected against biologically relevant protein targets are G-rich sequences that can fold into stable G-quadruplex (G4) structures. Aiming at disseminating novel inspiring ideas within the scientific community in the field of G4-structures, the emphasis of this review is placed on: 1) recent advancements in SELEX technology for the efficient and rapid identification of new candidate aptamers (introduction of microfluidic systems and next generation sequencing); 2) recurrence of G4 structures in aptamers selected by SELEX against biologically relevant protein targets; 3) discovery of several G4-forming motifs in important regulatory regions of the human or viral genome bound by endogenous proteins, which per se can result into potential aptamers; 4) an updated overview of G4-based aptamers with therapeutic potential and 5) a discussion on the most attractive G4-based aptamers for diagnostic applications. This article is part of a Special Issue entitled "G-quadruplex" Guest Editor: Dr. Concetta Giancola and Dr. Daniela Montesarchio. •Oligonucleotide aptamers and methods for their selection against specific targets•The recurrence of G-quadruplex (G4) motifs in oligonucleotide aptamers•G4-forming aptamers in therapeutic applications as drugs and drug delivery systems•G4-forming aptamers in detection and diagnostic applications